Reading Card and Index Card Match as a Learning Media in Mathematics Subject Materials of Fractions - Nining Puji Lestari; Nur'im Septi Lestari (JURNAL PENDIDIKAN MIPA, 2023)
The application of Reading Card and Index Card Matching strategies in Mathematics is done in a fun way. The implementation repeats the material that has been given before. emphasis on numeracy skills. The focus of this research is how to apply the Reading Card and Index Card Match strategies in Mathematics in class IV MI Islamiyah Jatirogo, Jatirogo District, Tuban Regency. This research sample uses 15 students. The method in this research is qualitative. Based on the research conducted, it can be concluded that the application of the Reading Card and Index Card Match strategies applied in learning Mathematics has been carried out well. The teacher has been able to make lesson plans well, namely by making lesson plans and preparing media in the form of well-matched cards. In the implementation of learning the teacher has been able to carry out learning steps with the Reading Card and Index Card Match strategies. In the evaluation activities, the teacher carried out the evaluation well so that it was seen that with the Reading Card Match and Index Card Match strategies the student learning outcomes were satisfactory so that this strategy was used again in subsequent learning.